Bringing life history theory into relationship science. Issue 1 (28th March 2019) - Simpson, Jeffry A.
Abstract : In this article, I review three longitudinal studies that have investigated how exposure to more versus less predictable environments shunt individuals down different developmental pathways. After describing key principles of life history theory and how stress can shape social development over time, I discuss an interrelated set of findings from the Minnesota Longitudinal Study of Risk and Adaptation. Collectively, these studies reveal the pathways through which exposure to more unpredictable, chaotic early‐life environments prospectively forecast engaging in riskier behaviors and shorter‐term, more opportunistic, and less investing orientations to mating and parenting in one or both genders. I conclude by discussing the broader goals underlying this program of research.